2019
DOI: 10.1155/2019/2735050
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pharmacological Mechanism of the Herb Pair “HuangLian-GanJiang” against Colorectal Cancer Based on Network Pharmacology

Abstract: Since the herb pair Huang Lian-Gan Jiang (HL-GJ) was put forward as conventional compatibility for cold-heat regulation in the middle energizer in the theory of Traditional Chinese Medicine (TCM), their therapeutic effects were observed on the prevention and treatment of intestinal inflammation and tumors including colorectal cancer (CRC). However, the active compounds, crucial targets, and related pathways of HL-GJ against CRC remained unclear. The purpose of this research was to establish a comprehensive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…The treatment of cancer under the holistic or systemic view of TCM has the characteristics of overall regulation with multi-molecular, multi-targets, multi-function, and multi-pathways, which is consistent with the principle of systems biology and network pharmacology. It has been widely applied in effective mechanisms of TCM treatments ( Zhang et al, 2013 ; Cai et al, 2018 ; Wu et al, 2019a ) and also applied in the research of Chinese herbal formulae on CRC treatment ( Liu et al, 2018b ; Gong et al, 2019 ). This study further investigated the effective mechanisms of BSJPJDD by transcriptomics, proteomics, network pharmacology analysis, and experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cancer under the holistic or systemic view of TCM has the characteristics of overall regulation with multi-molecular, multi-targets, multi-function, and multi-pathways, which is consistent with the principle of systems biology and network pharmacology. It has been widely applied in effective mechanisms of TCM treatments ( Zhang et al, 2013 ; Cai et al, 2018 ; Wu et al, 2019a ) and also applied in the research of Chinese herbal formulae on CRC treatment ( Liu et al, 2018b ; Gong et al, 2019 ). This study further investigated the effective mechanisms of BSJPJDD by transcriptomics, proteomics, network pharmacology analysis, and experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we selected the candidate compounds based on OB and DL properties. As suggested by the TCMSP database, OB ≥ 30% and DL ≥ 0.18 were used as the screening criteria, and the compounds whose OB ≥ 30% and DL ≥ 0.18 were selected for subsequent experiments [ 25 ]. We searched the oral bioavailability of all the compounds of Dangshen on PubMed.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also suggested that one of the major components of HLT, Huanglian, has a valuable effect in the treatment of Alzheimer's disease and brain injury (12,13). Furthermore, Huanglian has also been effective in treating certain types of cancer (14)(15)(16)(17).…”
Section: Network Pharmacological Systems Study Of Huang-lian-tang Inmentioning
confidence: 99%